In situ Parthenogenetic Doubled Haploid Production in Melon “Piel de Sapo” for Breeding Purposes - Hooghvorst, Isidre; Torrico, Oscar; Hooghvorst, Serge; Nogués, Salvador (Frontiers in Plant Science, 2020)
Doubled haploids in cucurbit species are produced through in situ parthenogenesis via pollination with irradiated pollen for further use as parental lines for hybrid F1 production. In this study, seven genotypes of melon ‘Piel de Sapo’ were appraised for agronomic traits and pathogen resistances to evaluate its commercial value and used as donor plant material for the parthenogenetic process. Then, in situ parthenogenetic capacity of melon ‘Piel de Sapo’ germplasm was evaluated and optimized. Several steps of the parthenogenetic process were assessed in this study such as melon fruit set after pollination with irradiated pollen, haploid embryo obtention, in vitro germination and growth of parthenogenetic embryos and plantlets, in vitro and in vivo chromosome doubling with colchicine or oryzalin and fruit set of doubled haploid lines. Parthenogenetic efficiencies of ‘Piel de Sapo’ genotypes showed a high genotypic dependency during the whole process. Three different methods were assayed for parthenogenetic embryo detection: one-by-one, X-ray and liquid medium. X-ray radiography of seeds was four times faster than one-by-one method and jeopardized eight times less parthenogenetic embryo obtention than liquid medium. One third of melon fruits set after pollination with irradiated pollen contained at least one parthenogenetic embryo. The 50.94% of the embryos rescued did not develop into plantlets because failed to germinate or plantlet died at the first stages of development because of deleterious gene combination in haploid homozygosity. The distribution of the ploidy-level of the 26 parthenogenetic plantlets obtained was: 73.08% haploid, 23.08% spontaneous doubled haploid and 3.84% mixoploid. Two in vitro chromosome doubling methods, with colchicine or oryzalin, were compared with a third in vivo colchicine method. In vivo immersion of apical meristems in a colchicine solution for 2 h showed the highest results of plant survival, 57.33%, and chromosome doubling, 9.30% mixoploids and 20.93% doubled haploids. Fruit set and seed recovery of doubled haploids lines was achieved. In this study, doubled haploid lines were produced from seven donor genotypes of melon ‘Piel de Sapo’, however, further improvements are need in order to increase the parthenogenetic efficiency.